MODEL DAN IMPLEMENTASI KURIKULUM INTEGRATIF DI SATUAN PENDIDIKAN - Yusadi, Ardini; Sabri, Ahmad (UIN Imam Bonjol Padang, 2024)
An integrative curriculum combines several subjects into one unit. This curriculum eliminates subject boundaries. The units are united by a common theme with interrelated material content. This research is a literature study using the systematic literature review (SLR) method which consists of 6 stages, namely planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection and data analysis. This research aims to examine the Model and Implementation of Integrative Curriculum in Education Units. In general, the integrative curriculum is a model for combining basic knowledge with learning experiences that suit students' future needs. Implementation of an integrative-holistic curriculum is carried out in three forms. First, with the package system. Second, with a system that is integrated with general subjects as a basis for value in scientific development. And third, in the form of extra-curricular activities and hidden curriculum in the form of habituation. Curriculum evaluation is carried out by reviewing curriculum implementation in the form of learning evaluation.